2015
DOI: 10.1007/s00203-015-1173-5
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of an exopolysaccharide-producing heavy metal-resistant Halomonas sp. MG

Abstract: An exopolysaccharide (EPS)-producing heavy metal-resistant Gram-negative bacterium was isolated from ore-contaminated soil. The selected strain was identified by 16S rDNA sequencing and designated as Halomonas sp. MG. Phylogenetic analysis of the gene sequence showed its close similarity with Halomonas sp. Field emission scanning electron microscopy analysis revealed that the EPS had a porous structure with small pores. X-ray diffractograms showed the non-crystalline nature of the EPS. Further, FTIR spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Interestingly, heavy metal tolerance of BRI 36 in terms of maximum tolerable concentration (MTC) was found to increase considerably with an increase in EPS produced by the isolate. Role of EPS in metal resistance has been previously documented by various researchers [14][15][16][17]. These observations prompted us to undertake studies on EPS production, and its effect on heavy metal tolerance of Kocuria sp.…”
Section: Introductionmentioning
confidence: 87%
“…Interestingly, heavy metal tolerance of BRI 36 in terms of maximum tolerable concentration (MTC) was found to increase considerably with an increase in EPS produced by the isolate. Role of EPS in metal resistance has been previously documented by various researchers [14][15][16][17]. These observations prompted us to undertake studies on EPS production, and its effect on heavy metal tolerance of Kocuria sp.…”
Section: Introductionmentioning
confidence: 87%
“…The FESEM was used to study the microstructures of the EPS. [ 35 ] The FESEM images showed multiple fissures and pores in the EPS microstructures (Figure 1B). Multiple reports indicated the porous microstructure nature of the EPS and suggested as potential thickeners, viscosifiers, texturizers, and eventually as stabilizing agents utilized in the food industry.…”
Section: Resultsmentioning
confidence: 99%
“…Field emission scanning electron microscopy was a known technique for studying the microstructure of EPSs. 32 As shown in Figure 2A-B, the EPSs micrographs are presented a porous and three-dimensional structure and several crevices were observed in their microstructure. There were many studies on microstructures of EPSs which some of them have reported the porous nature of EPS.…”
Section: Morphology and Water Holding Capacity Of Epssmentioning
confidence: 85%
“…There were many studies on microstructures of EPSs which some of them have reported the porous nature of EPS. [32][33][34] Ramirez suggested that EPS of porous nature can be used as a thickener, texturizer, viscosifier and stabilizing agent in food industry. 4 The water holding capacity of the EPSs was 519 ± 18.5%.…”
Section: Morphology and Water Holding Capacity Of Epssmentioning
confidence: 99%